Self‐control in crows, parrots and nonhuman primates - Miller, Rachael; Boeckle, Markus; Jelbert, Sarah A.; Frohnwieser, Anna; Wascher, Claudia A. F.; Clayton, Nicola S. (Wiley interdisciplinary reviews. Cognitive science, 2019)
Self‐control is critical for both humans and nonhuman animals because it underlies complex cognitive abilities, such as decision‐making and future planning, enabling goal‐directed behavior. For instance, it is positively associated with social competence and life success measures in humans. We present the first review of delay of gratification as a measure of self‐control in nonhuman primates, corvids (crow family) and psittacines (parrot order): disparate groups that show comparable advanced cognitive abilities and similar socio‐ecological factors. We compare delay of gratification performance and identify key issues and outstanding areas for future research, including finding the best measures and drivers of delayed gratification. Our review therefore contributes to our understanding of both delayed gratification as a measure of self‐control and of complex cognition in animals. This article is categorized under: Cognitive Biology > Evolutionary Roots of Cognition Psychology > Comparative Psychology Examples of delayed gratification tasks. (a) Exchange task with a corvid: subject can choose to swap a token (e.g., bottle top) for a reward after a delay; (b) Intertemporal choice: monkey can select the immediately available reward or wait for the delayed reward from a rotating tray.